2014
DOI: 10.1124/dmd.114.062067
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Wuzhi Tablet (Schisandra sphenanthera Extract) on Acetaminophen-Induced Hepatotoxicity through a Mechanism Distinct from N-Acetylcysteine

Abstract: Acetaminophen (APAP) hepatotoxicity is the most common cause of drug-induced liver injury and N-acetylcysteine (NAC) is the primary antidote of APAP poisoning. Wuzhi tablet (WZ), the active constituents well identified and quantified, is a preparation of an ethanol extract of Schisandra sphenanthera and exerts a protective effect toward APAP-induced hepatotoxicity in mice. However, the clinical use of WZ to rescue APAP-induced acute liver injury and the mechanisms involved in the therapeutic effect of WZ remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 34 publications
(41 reference statements)
0
24
0
Order By: Relevance
“…The patient was consuming the supplement Green Tea Fat Burner ® , whose components, other than green tea, are not known as causing hepatotoxicity; on the contrary, some of them are considered to possess hepatoprotective effects (Fan et al 2015;Huang et al 2011). However, the young man was consuming also other supplements such as Nopal ® , an extract from cactus of Opuntia genus, used as source of dietary fibers in the management of overweight (Grube et al 2013), GNC Mega Men Sport ® , a complex mixture containing numerous vitamins, minerals among which are chromium, branched chain amino acids, l-carnitine, lycopene, choline, zeaxanthin, astaxanthin, alpha-lipoic acid and others and, finally, whey protein.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was consuming the supplement Green Tea Fat Burner ® , whose components, other than green tea, are not known as causing hepatotoxicity; on the contrary, some of them are considered to possess hepatoprotective effects (Fan et al 2015;Huang et al 2011). However, the young man was consuming also other supplements such as Nopal ® , an extract from cactus of Opuntia genus, used as source of dietary fibers in the management of overweight (Grube et al 2013), GNC Mega Men Sport ® , a complex mixture containing numerous vitamins, minerals among which are chromium, branched chain amino acids, l-carnitine, lycopene, choline, zeaxanthin, astaxanthin, alpha-lipoic acid and others and, finally, whey protein.…”
Section: Discussionmentioning
confidence: 99%
“…proliferation-related genes and may promote compensatory liver regeneration to prevent hepatic failure, suggesting that WZ may act as a therapy drug to limit liver injury (Fan et al, 2015). However, whether WZ can directly facilitate liver regeneration after liver resection and what related mechanisms are involved remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that WZ exerts significant hepatoprotective effects against acetaminophen-induced acute liver injury (Bi et al, 2013;Fan et al, 2015). This hepatoprotection, in large part, contributes to the ability of WZ to induce the expression of hepatocyte dmd.aspetjournals.org…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations